2010
DOI: 10.1073/pnas.0914356107
|View full text |Cite
|
Sign up to set email alerts
|

Mutant EGFR is required for maintenance of glioma growth in vivo, and its ablation leads to escape from receptor dependence

Abstract: Epidermal growth factor receptor (EGFR) gene amplification is the most common genetic alteration in high-grade glioma, and ≈50% of EGFR-amplified tumors also harbor a constitutively active mutant form of the receptor, ΔEGFR. Although ΔEGFR greatly enhances tumor growth and is thus an attractive target for anti-glioma therapies, recent clinical experiences with EGFR kinase inhibitors have been disappointing, because resistance is common and tumors eventually recur. Interestingly, it has not been established whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
73
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 28 publications
1
73
0
1
Order By: Relevance
“…Thus, we examined the effects of Dox on the activity of cell-signaling factors known to be regulated by both EGFRvIII and uPAR. In Dox-treated U373MG cells, phospho-ERK (P-ERK) was slightly decreased and P-STAT3 was more substantially decreased, as anticipated (15).…”
supporting
confidence: 54%
See 2 more Smart Citations
“…Thus, we examined the effects of Dox on the activity of cell-signaling factors known to be regulated by both EGFRvIII and uPAR. In Dox-treated U373MG cells, phospho-ERK (P-ERK) was slightly decreased and P-STAT3 was more substantially decreased, as anticipated (15).…”
supporting
confidence: 54%
“…Failure of EGFR-targeting therapeutics to induce sustained remission may reflect mutations in gene products downstream of the EGFR, such as the tumor suppressor PTEN, or activation of alternative receptors with overlapping cell-signaling activity (10,(12)(13)(14). Mukasa et al (15) developed a derivative of the U373MG GBM cell line in which EGFRvIII is expressed under the control of a doxycycline (Dox)-repressible promoter system. These cells establish xenografts in mice only if EGFRvIII is expressed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, recent studies have demonstrated that EGFRvIII is required for tumor maintenance in glioma (Mukasa et al, 2010). The EGFR tyrosine kinase inhibitor gefitinib has been evaluated in a number of clinical trials for GBM; however, results have been disappointing (Rich et al, 2004;Lieberman et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Parental U87MG cells and U87MG cells that overexpress wild-type EGFR (WT-EGFR) or express EGFRvIII were described previously (43). Parental U373MG cells, U373MG cells that overexpress WT-EGFR, and U373MG cells that express EGFRvIII under the control of a doxycycline-repressible promoter also were previously described (44). These cells were cultured in the presence of puromycin (1 g/ml) and geneticin (200 g/ml), with or without doxycycline (1 g/ml).…”
Section: Methodsmentioning
confidence: 99%